2006
DOI: 10.1007/s10909-006-9227-3
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Bose–Einstein Condensation by Disorder

Abstract: Recent experiments suggest that Bose-Einstein condensation (BEC) in liquid 4 He can be localized when the liquid is confined in porous media. We demonstrate in a simple model of hard core bosons using Monte Carlo that the condensate can be separated into two parts. The two regions of condensate are separated by a region of uncondensed fluid that forms in response to a local attractive external potential. The aim is to illustrate that separated condensates, and therefore localized BEC, can be created in porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…For strong enough potential wells, we see localization of the condensate to islands and loss of superflow along the lattice. The localization of the condensate to islands that we see could be similar to that observed in disordered systems such as helium in porous media [37][38][39][40][41][42] because the localization in porous media is thought to be depletion mediated 41,42 rather than caused by disorder per se. Depletion can localize the condensate whenever there are sharp changes in the density profile and that can happen either in periodic or aperiodic ͑disor-dered͒ systems.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For strong enough potential wells, we see localization of the condensate to islands and loss of superflow along the lattice. The localization of the condensate to islands that we see could be similar to that observed in disordered systems such as helium in porous media [37][38][39][40][41][42] because the localization in porous media is thought to be depletion mediated 41,42 rather than caused by disorder per se. Depletion can localize the condensate whenever there are sharp changes in the density profile and that can happen either in periodic or aperiodic ͑disor-dered͒ systems.…”
Section: Discussionsupporting
confidence: 75%
“…The state with BEC localized to islands is often denoted as a Bose glass. In a recent paper, Shams et al 42 have shown through variational Monte Carlo ͑MC͒ simulation at 0 K that depletion-mediated localization is indeed a plausible effect in systems where there are regions of extremely high density.…”
Section: Introductionmentioning
confidence: 99%
“…Вивчення термодинамiчних властивостей 4 He сьогоднi проводиться не тiльки для рiдкого [19,18,17] чи газоподiбного стану [20], багато робiт присвяченi i твердому стану [25,24,23,22,21]. Активно вивчається термодинамiка плiвок [28,26,27] та сумiшей [30,29], а також поведiнка 4 He в рiзних середовищах [33,32,31].…”
unclassified
“…The gapless modes that propagate along a physical boundary, while they are exponentially decaying away from the physical boundary, are gapless boundary modes or edge states. 12 Examples for the occurrence of surface excitations in bounded BECs comprise, for example, superfluid 4 He (helium II) confined in pores, 13 self-bound condensates at the low-density surface of superfluid helium 14 , as well as surface states of a BEC trapped in an external potential 15 , or surface states of other media with a defocusing nonlinearity. 16 They are of fundamental interest since they reveal the role of quantum effects on the excitation character (i.e., effects which are not existing on the classical level) in restricted geometries.…”
Section: Introductionmentioning
confidence: 99%